Long-term serving political leadership : an impediment to a dream of an African Renaissance - Maoto, M. K. (International Conference on Public Administration and Development Alternatives, 2018)
There are many questions that arise about Africa as a continent. The continent is well-endowed with natural resources and yet it remains the world’s poorest continent. Its resources have been misused by long serving political leaders which subsequently resulted in the promotion of conflicts and corruption and left the continent in a state of paralysis. Most African states have been ravaged by ongoing conflicts and civil wars characterised by political violence and unspeakable human rights violations, thus making peace and stability a mirage. The sad reality is that Africa is home to long term serving political leaders. The kernel of the paper rests on the fact that there is a nexus between long serving political leadership, conflict and corruption and it is against this background that this paper investigates among others, the problems associated with long term serving political leadership, their contribution towards the promotion of corruption and conflict among their states and citizens as well as some leadership theories. Africa as a continent is facing a financial and economic growth turmoil. Again, this is associated with rampant corruption where freedom of expression by media is restricted and in some instances, the independence of the judiciary is paralyzed or non-existent. Moreover, it still has presidents who are jailing opposition leaders, manipulating the army and police force to clamp down on dissent, and promising their citizens change which remains but a dream. It is for these instances that, leaders refuse to vacate their offices because they have engaged themselves in corruption accompanied by gross human right violations and as such they would rather prefer to die in presidential offices than to face the lifelong humiliations and prosecutions once they leave their positions. This paper is conceptual in nature and the review is conducted based on books, peer reviewed articles, conference papers and chapters in books. This paper concludes by recommending that for African countries to achieve socio-economic growth and political stability which could serve as a moment of great reawakening, a moment of a new dawn, they require honest, selfless and legally responsible leaders who would transplant the moral and gallant supremacy. Again, the creation of a conducive environment which will be thriving and advantageous for the people to claim back their powers and use their resources as opulently as they deserve to equip both their social, economic and political wellbeing. Furthermore, the issue of term of office by presidents and the creation of communal doctrine guiding leaders have to be revisited. Keywords: Conflict, Corruption, Leadership, New dawn, Politics
Article published in: The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Conflict; Corruption; Leadership; New dawn; Politics; Political leadership - Africa; Political corruption - Africa; 9 Africa - Politics and government